2021
DOI: 10.1002/mds.28508
|View full text |Cite
|
Sign up to set email alerts
|

Voice Analysis with Machine Learning: One Step Closer to an Objective Diagnosis of Essential Tremor

Abstract: A BS TRACT: Background: Patients with essential tremor have upper limb postural and action tremor often associated with voice tremor. The objective of this study was to objectively examine voice tremor and its response to symptomatic pharmacological treatment in patients with essential tremor using voice analysis consisting of power spectral analysis and machine learning. Methods: We investigated 58 patients (24 men; mean age ± SD, 71.7 ± 9.2 years; range, 38-85 years) and 74 age-and sex-matched healthy subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
1
31
0
2
Order By: Relevance
“…Indeed, a recent study demonstrated that the repeatability of automatically extracted speech features for dysarthria assessment using OpenSMILE is low. 4 Therefore, to demonstrate the impropriety of such a design, we performed two additional experiments to challenge the original analysis by Suppa et al 1 First, we generated a random vector of values ranging between 0 and 1 to substitute 6139 hypothetical voice features across 58 hypothetical patients. Second, we used OpenSMILE 3 to extract 6139 voice features via sustained phonation /a/ paradigm recorded using standardized settings 5 from two groups of healthy speakers designed to be age-and gender matched to the original ET VT+ and ET VT-groups (Fig.…”
Section: Reproducibility Of Voice Analysis With Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a recent study demonstrated that the repeatability of automatically extracted speech features for dysarthria assessment using OpenSMILE is low. 4 Therefore, to demonstrate the impropriety of such a design, we performed two additional experiments to challenge the original analysis by Suppa et al 1 First, we generated a random vector of values ranging between 0 and 1 to substitute 6139 hypothetical voice features across 58 hypothetical patients. Second, we used OpenSMILE 3 to extract 6139 voice features via sustained phonation /a/ paradigm recorded using standardized settings 5 from two groups of healthy speakers designed to be age-and gender matched to the original ET VT+ and ET VT-groups (Fig.…”
Section: Reproducibility Of Voice Analysis With Machine Learningmentioning
confidence: 99%
“…1). 1 For both scenarios, we performed a similar procedure as reported in Suppa et al 1 ; in short, the generated/extracted features underwent feature selection, and 20 best-ranked features were used to train a linear kernel support vector machine classifier with a 10-fold cross-validation procedure.…”
Section: Reproducibility Of Voice Analysis With Machine Learningmentioning
confidence: 99%
“…[3][4][5] We therefore suggest that the sustained emission of a vowel could be the most appropriate technical solutions for preventing linguistic confounding and achieving standardized worldwide procedures. [3][4][5] Finally, the recording guidelines of Rusz et al 1 require voice samples collected only in a specialized laboratory using dedicated hi-tech audio recorders under expert supervision. We have recently proposed an alternative solution consisting of voice recordings acquired by currently available smartphones that can simplify the experimental procedures in a more ecologic scenario and provide the background for future application in the context of telemedicine.…”
mentioning
confidence: 99%
“…1 However, recent data from our group show similar results when comparing the sustained emission of vowels and sentences (eg, connected speech). [3][4][5] We therefore suggest that the sustained emission of a vowel could be the most appropriate technical solutions for preventing linguistic confounding and achieving standardized worldwide procedures. [3][4][5] Finally, the recording guidelines of Rusz et al 1 require voice samples collected only in a specialized laboratory using dedicated hi-tech audio recorders under expert supervision.…”
mentioning
confidence: 99%
“…We hope that the scientific impact of our first analysis is now much more clear. 2 The second point raised by Rusz et al 1 concerns our tool kit for voice feature extraction. We believe that the tool kit Receiver operating characteristic curves calculated with a support vector machine using 20 best-ranked features selected from 6139 features to differentiate two groups (34 and 24 samples, respectively) formed by (A) random values ranging from 0 to 1 and (B) healthy speakers with voice analysis based on sustained phonation paradigm extracted via OpenSMILE toolkit.…”
mentioning
confidence: 99%